The characteristics of the flow field over the mid-upper fuselage of Lancaster P. A. 474 - Burrows, F. M. (College of Aeronautics, 1956)
This note describes a series of tests conducted to determine the characteristics of the flow field over the mid-upper fuselage of. Lancaster P. A, 474. The range of the tests was to include a determination of the distributions of total head, static pressure and velocity together with the flow directional characteristics in the pitching plane for a number of aircraft flight configurations as listed in paragraph 1. 2. Curves are presented in Figs. 9, 20 - 25, showing the flow directional characteristics and the distributions of static pressure and velocity in the region of investigation.